Analisis Kualitas Air Sumur Bor Berdasarkan Kesesuaian Higiene Sanitasi di Kelurahan Ujung Gurun Kecamatan Padang Barat Kota Padang - Fajri, Fajri; Hermon, Dedi; Andrian, Andrian (Al-DYAS, 2024)
This study aims to determine the quality of well water in Ujung Gurun Village, Padang City and the factors that influence it. The research method used is quantitative research by utilizing primary data taken from several well samples in the area. The parameters tested include pH, Total Dissolved Solids (TDS), iron (Fe), manganese, and lead.The results showed that most of the water quality parameters have met the requirements, except for the iron (Fe) content which is in the range of 1.7 to 7.5 Mg/L, exceeding the set limit. Overall, the quality of well water in Ujung Gurun Village is quite good, but further processing is needed to reduce the iron content to comply with the applicable regulations.The factors that affect the water quality in this area are poor and clogged drainage, as well as the possibility of seawater intrusion. Improvement and maintenance of the drainage system as well as appropriate water treatment need to be carried out to improve the quality of well water in Ujung Gurun Village, Padang City.